Study on the Application of Gob-Side Entry Retaining via Roof Cutting under the Condition of a Hard Thick Roof. (28th July 2022) - Zhu, Daoyong; Zhang, Huyue; Su, Yi
Abstract : To solve the problem of instability and failure of a roadway in the Dianping coal mine working face under the condition of traditional gob-side entry retaining, a mechanical model was established for analysis. The reasons for the damage are as follows: (1) the mining height is high, and the hard thick old roof exhibits large space for rotation and subsidence; (2) the retained roadway includes a large section; and (3) the mining impact is strong, and the adaptability of traditional cable is poor. Therefore, the technologies of "roof-cutting type gob-side entry retaining" were proposed and the principle was analyzed. Numerical simulation analysis of displacement and stress field under two processes was performed. The results indicated that the peak value of side abutment pressure decreased from 20.54 to 18.24 MPa due to the roof cutting (a decrease of 11%). The advance stress was less than the stress value under traditional conditions. When compared with the traditional conditions, the deformation of the roadway decreased by more than 50%. Finally, field monitoring was performed, and the results showed that under the condition of roof cutting, the deformation corresponded to the most severe within the range of 30–80 m behind the working face. After 80 m, the deformation gradually stabilized, and the maximum convergence between the roof and floor was 210 mm. Along the inclined direction, the stress of the hydraulic support in the middle part was the highest, the stress in the uncut side was second highest, and that in the roof-cutting side was the lowest. The periodic weighting interval on the roof-cutting side was the highest, and the transverse influence range of the roof cutting along the working face corresponded to 29.5 m.